Total Quality Management (TQM) Tahfidz Al-Qur’an Islamic Boarding School: A Study at Tahfidz Daarul Qur’an Islamic Boarding School Tangerang - Arribath, Abdul Hamid; Suradika, Agus; Sopa, Sopa (Technium Social Sciences Journal, 2021)
Generally, there is a gap in Total Quality Management (TQM) of education in the application of the management of tahfidz al-Qur’an in Islamic boarding schools. The purpose of this study is to determine the Total Quality Management (TQM) model of the Tahfidz al-Qur’an Islamic Boarding School which is based on the Edward Sallis Education TQM model, in order to realize the National Education Standards (SNP). This research uses the descriptive qualitative method. The research site is a modern Islamic boarding school at the Tahfidz Daarul Qur’an Islamic Boarding School, Tangerang City, Banten, Indonesia. Data collection techniques in this study used in-depth interviews, observation, and literature. While data analysis in making decisions using Miles and Huberman (data reduction, data presentation, and drawing conclusions). The results showed that there were 12 elements of TQM Pesantren Tahfidz al-Qur’an, including leadership, commitment to quality, customer satisfaction, continuous improvement, integrated curriculum, and learning evaluation, learning media and models, education & training, infrastructure standards, finance and financing, public relations and pesantren, unity of vision and mission, and objectives, as well as analyzing the situation.